(untitled) (Research, Society and Development, 2020)
The acceleration of environmental degradation, poverty and the relations between consumption and production modes it awakened conscience on the part of society to the teaching that took into account the relations between Science, Technology, Society and Environment (STSE) for the citizen’s scientific and environmental training. In order to understand how these relations are developed in the ​​Natural Sciences area, we present in this article the result of a research of the type state of knowledge carried out at the Brazilian Digital Library of Theses and Dissertations (BDTD) in the period from 2013 to 2019 that had as aim to know as STSE relations has been developed by researchers in this area of knowledge. We selected 44 productions that were analyzed according to Fiorentini. The data revealed that since 2015, the number of researches has not varied much in the examined years. The Universidade Estadual Paulista (Unesp), Universidade Federal Fluminense (UFF) and Universidade Federal de Sergipe (UFS) were the higher education institutions that developed the largest number of research and the STSE relations are developed by researchers, mostly by construction and application of teaching sequences whose themes are socioscientific issues.